WATER SUITABILITY FOR SEAWEED Kappaphycus alvarezii CULTURE USING SENTINEL-2A IN AENG BATU-BATU VILLAGE, TAKALAR REGENCY - Elis Safitri; Ardi Eko Mulyawan; Nuraeni L. Rapi (Jurnal Perikanan Unram, 2024)
Certain individuals residing in Aeng Batu-Batu Village are engaged in the cultivation of seaweed (Kappaphycus alvaezii). However, the community encounters a challenge in identifying suitable areas for seaweed farming. The objective of this study is to assess the appropriateness of the waters for cultivating seaweed. The present study was carried out in June 2023. The exploration method utilized in this study seeks to ascertain the degree of suitability exhibited by the waters for seaweed cultivation. An Aeng Batu-Batu Village sampling procedure was implemented, consisting of three repetitions. A unique set of water quality parameters was acquired at each sampling point. In descending order, the values of each parameter are presented. Current velocity (23.62-11.47 cm/s), depth (5-2 meters), water clarity (3.35-2.3 meters), pH (7.91-7.73), salinity (27-23 ppt), temperature (30-28 °C), phosphate (0.0362-0.0122 mg/L), and nitrate (0.069-0.014 mg/L). The water suitability matrix indicates that 185.06 ha of the valley's water is suitable for seaweed cultivation in Aeng Batu-Batu Village, while 0.3 hectare of the valley's water is unsuitable for seaweed cultivation.